CERITA TENTANG PANGAN DAN PAKAN DI DAERAH KODI, SUMBA BARAT DAYA - Wisma Nugraha Christianto (Universitas Gadjah Mada, 2019)
Beginning with the question of why the people of Sumba, especially in Kodi, Southwest Sumba Regency, East Nusa Tenggara Province, feel ‘embarrassed’ to tell the outsiders that they still consume tubers as a staple food, this paper unfolds the story of food and fodder based on the recollection of the community. They eat rice mixed with corn every day and find such food tasty and fulfilling. They solely eat rice during important ritual ceremonies (wedding, funeral, and other traditional rituals). Eating steamed or roasted tubers, accompanied by coffee or sweet tea, has been their morning or afternoon habit while engaging in a conversation with family members. However, tubers become staple food during the hunger season. The data were collected using Participatory Research (RAP) method, or also known as the Action Research. The RAP method also offers ‘learning by doing’ technique that focuses on dialogues between researchers and community members or groups of people to bring together knowledge, experience, and ideas to obtain the desired results and devise future actions. The stories were recorded and documented and later combined with the results of the literature study. The records of the stories were transcribed and then analyzed using the Intertextual method. Rice is a symbol of prosperity and civilization, making it an important food in the ritual sphere in Kodi. However, due to the condition of nature and the persistent drought and water scarcity, rice production becomes highly dependent on rain. The government programs have not been able to solve water management issues in the region.